2004
DOI: 10.1002/clc.4960271304
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk stratification and cardiovascular risk factors associated with erectile dysfunction: Assessing cardiovascular risk in men with erectile dysfunction

Abstract: Summary: Cardiovascular risk factors are known to be associated with the presence of erectile dysfunction (ED), and ED is more common in men with cardiovascular disease (CVD). The Princeton Guidelines provide a strategy for assessing cardiac risk and planning a safe return to sexual activity. Men at low risk, who have fewer than three cardiac risk factors, can resume intercourse with very little concern for an untoward cardiac event. Men at high risk need to have their primary disease controlled, and should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…Principal among these risk factors are DM, hypercholesterolaemia (HcH), dyslipidaemia, cigarette smoking, hypertension and possibly HHC. [2][3][4][5][6] This association points to a common aetiology in both scenarios.…”
Section: Risk Factors For Ed: Role Of Oxygen-free Radicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Principal among these risk factors are DM, hypercholesterolaemia (HcH), dyslipidaemia, cigarette smoking, hypertension and possibly HHC. [2][3][4][5][6] This association points to a common aetiology in both scenarios.…”
Section: Risk Factors For Ed: Role Of Oxygen-free Radicalsmentioning
confidence: 99%
“…The treatment of ED has also taken on new importance in that ED is a predictor of more serious CVDs. [4][5][6] It follows, also, that those therapies that prove successful in preventing in ED may prevent longer term CVDs that include atherogenesis, myocardial infarction and stroke.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smoking, obesity, hypertension, diabetes and dyslipidemias contribute to ED in elderly men. 20,23,45 Although vascular comorbidities are associated with ED, a study using neural computational networks identified SHIM scores representing moderate ED correlated with age, total testosterone and a depression scale. 46 Testosterone declines with age in men at a rate of 1-2% a year.…”
Section: Sd With Age In Menmentioning
confidence: 99%
“…ED may act as a marker for silent coronary artery disease and may therefore precede a coronary event; this concept is reinforced by ED and vascular disease sharing the same risk factors. [18][19][20][21][22] In August 2003, the MHI (Minority Health Institute) convened an Expert Advisory Panel of cardiologists and urologists to design a new practice model algorithm that uses ED as a clinical tool for the early identification of men with systemic vascular disease. The MHI algorithm noted ED as a marker for the presence of cardiovascular disease and suggested that ED may well be a cardiovascular risk equivalent warranting aggressive secondary prevention management strategies, even in the absence of other cardiac or peripheral vascular symptoms.…”
Section: Discussionmentioning
confidence: 99%